2021
DOI: 10.1021/acsomega.1c05020
|View full text |Cite
|
Sign up to set email alerts
|

Noncatalytic Oxidative Coupling of Methane (OCM): Gas-Phase Reactions in a Jet Stirred Reactor (JSR)

Abstract: Oxidative coupling of methane (OCM) is a promising technique for converting methane to higher hydrocarbons in a single reactor. Catalytic OCM is known to proceed via both gas-phase and surface chemical reactions. It is essential to first implement an accurate gas-phase model and then to further develop comprehensive homogeneous–heterogeneous OCM reaction networks. In this work, OCM gas-phase kinetics using a jet-stirred reactor are studied in the absence of a catalyst and simulated using a 0-D reactor model. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 78 publications
0
10
0
Order By: Relevance
“…The OCM gas phase kinetic study was conducted using a jetstirred reactor (JSR), similar to previous studies by this group. [16,39] In brief, a spherical JSR (volume of 76 cm 3 ) with four cross nozzles created stirring jet flows and mixed the inlet streams perfectly. The reactor was made from fused silica to minimize wall reactions.…”
Section: Experimental Setup and Reaction Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The OCM gas phase kinetic study was conducted using a jetstirred reactor (JSR), similar to previous studies by this group. [16,39] In brief, a spherical JSR (volume of 76 cm 3 ) with four cross nozzles created stirring jet flows and mixed the inlet streams perfectly. The reactor was made from fused silica to minimize wall reactions.…”
Section: Experimental Setup and Reaction Studymentioning
confidence: 99%
“…In a previous study by this group, some gas phase models from published methane-related homogenous-heterogeneous mechanisms were fine-tuned based on observations of their heterogeneous reactions, affecting the overall reliability of the mechanism. [16] For this reason, a La 2 O 3 /CeO 2 catalyst was synthesized and characterized, and the effect of CeO 2 addition on La 2 O 3 was investigated in this study. Not only was the overall performance tested, but an experimental study was also performed isothermally under various operating conditions, including temperatures, inlet space velocities, and CH 4 /O 2 ratios for kinetic study.…”
Section: Introductionmentioning
confidence: 99%
“…The developed model was validated against the original mechanism and jet stirred reactor (JSR) experiments. The details of the JSR experiments were reported in a different study (Wang et al, 2021). The study investigated the non-catalytic gas-phase chemistry in JSR experiments against literature mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the tuned gas-phase reactions negatively affect the surface kinetic rates optimization and accuracy. A comparison between different tuned and detailed gas-phase mechanisms against experimental performance was investigated by Wang et al (Wang et al, 2021).…”
Section: Previous Studies On the Ocm Reaction Kineticsmentioning
confidence: 99%
“…75 Catalytic OCM was first reported in 1982, and since then, significant research has been devoted to developing more efficient heterogeneous catalysts, designing reactors, and optimizing process parameters for this process. 76,77 The primary challenge in the process is to design efficient catalysts that allow forming ethylene selectively at high conversions of CH 4 without coke formation and catalyst degradation. Recently, Liu et al reported gaseous S 2 as an alternative oxidant to O 2 for the OCM into ethylene over Fe 3 O 4derived FeS 2 catalyst.…”
Section: Ethylenementioning
confidence: 99%